Socioeconomic position and urban environments as drivers of antimicrobial resistance? An ecological study in Germany, 2010 to 2019 - Niels Michalski (Eurosurveillance)
BACKGROUND Germany lacks comprehensive studies on the relationship between socioeconomic position (SEP) and antimicrobial resistance (AMR). AIM We assessed the association between area-level SEP and AMR infection and colonisation in Germany. METHODS In an ecological study design, we analysed statutory notifications of invasive meticillin-resistant Staphylococcus aureus (MRSA, n = 34,440) in 2010−2019, and colonisations and infections with carbapenem-resistant Acinetobacter spp. (CRA, n = 1,979) and Enterobacterales (CRE, n = 10,825) in 2017−2019. Area-level SEP was measured by the German index of socioeconomic deprivation (GISD), incorporating education, employment and income data. A multilevel Poisson regression analysis estimated the association between AMR incidence and GISD at district level, adjusting for age, sex, notification year and urbanisation degree. RESULTS Median ages of patients with carbapenem-resistant bacteria were between 66 (CRA colonisation) and 69 years (CRE infection). For MRSA infections, the median age was 74 years. Across each pathogen, approximately two thirds of patients were male. Estimated MRSA incidence was almost five times higher in districts with lowest vs highest area-level SEP (incidence rate ratio, IRR: 4.8; 95% CI: 2.8–8.2). This association was strongest in large cities (IRR: 9.1; 95% CI: 2.7–30.9), and sparsely populated rural districts (IRR: 6.5; 95% CI: 2.8–15.0). Associations of CRA (IRR: 0.6; 95% CI: 0.3–1.2) and CRE (IRR: 0.9; 95% CI: 0.6–1.4) infections with SEP were not statistically significant. CONCLUSION Lower area-level SEP and degree of urbanisation were associated with MRSA incidence, however, no associations were uncovered between SEP and CRA or CRE infections. Further individual-level research could explore if health behaviours, living/working conditions or healthcare access explain the findings. Socioeconomic conditions should be considered for AMR prevention and control.